2016
DOI: 10.1021/acs.analchem.6b03526
|View full text |Cite
|
Sign up to set email alerts
|

Toward Liquid Biopsy: Determination of the Humoral Immune Response in Cancer Patients Using HaloTag Fusion Protein-Modified Electrochemical Bioplatforms

Abstract: Autoantibodies raised against tumor-associated antigens have shown high promise as clinical biomarkers for reliable diagnosis, prognosis, and therapy monitoring of cancer. An electrochemical disposable biosensor for the specific and sensitive determination of p53-specific autoantibodies has been developed for the first time in this work. This biosensor involves the use of magnetic microcarriers (MBs) modified with covalently immobilized HaloTag fusion p53 protein as solid supports for the selective capture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Recently, a novel multiplexed electrochemical biosensor for the simultaneous detection of CRC-specific autoantibodies in plasma samples was developed by Garranzo-Asensio et al [48], similarly to that previously reported for a single tumor-associated antigen (TAA) (p53) [131]. The multiplexed immunosensor used HaloTag fusion proteins self-assembled on magnetic microparticles and amperometric detection at disposable SPCEs in the presence of the H 2 O 2 /HQ system ( Figure 17).…”
Section: Electrochemical Multibiosensing Of Crc-associated Biomarkersmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, a novel multiplexed electrochemical biosensor for the simultaneous detection of CRC-specific autoantibodies in plasma samples was developed by Garranzo-Asensio et al [48], similarly to that previously reported for a single tumor-associated antigen (TAA) (p53) [131]. The multiplexed immunosensor used HaloTag fusion proteins self-assembled on magnetic microparticles and amperometric detection at disposable SPCEs in the presence of the H 2 O 2 /HQ system ( Figure 17).…”
Section: Electrochemical Multibiosensing Of Crc-associated Biomarkersmentioning
confidence: 90%
“…Therefore, the level of serum p53 antibodies is a potential biomarker of high stability for minimally invasive cancer malignancy screening, monitoring, and prognosis [130]. Garranzo-Asensio et al [131] developed a biosensor based on magnetic beads (MBs) modified with covalently immobilized HaloTag fusion p53 protein as an electrochemical detection system ( Figure 6). After capturing the magnetic beads bearing the immunocomplexes onto screen-printed carbon working electrodes, the bio-recognition event was monitored by the amperometric readout generated by the enzymatic reduction of H 2 O 2 mediated by HQ, which revealed the level of p53 autoantibodies in the sample.…”
Section: Electrochemical Biosensing Of Protein Biomarkers Of Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…POCT is aimed at bringing immediate test results to the patient, physician, and care team, thereby increasing the likelihood that immediate clinical management decisions can be made. Although many immunoassays have been described for detecting clinically relevant antibodies, including ELISAs and new technologies employing nanoplasmonic biosensors or electrochemical detection 46 , these methods are impractical for POCT due to prolonged assay times and complicated procedures. Currently, solid-phase lateral flow immunoassays and miniaturized ELISAs have been developed for POCT.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, the main characteristics of novel biosensing scaffolds for the determination of cancer related-miRNAs [1][2][3] and autoantibodies [4] against tumor associated antigens (TAAs), relevant biomarkers considered for both early diagnosis and prognosis, will be presented. The developed methodologies, based on the coupling of attractive bioreceptors and bioassay formats, functionalized magnetic microcarriers, and electrochemical detection at disposable transducers, have demonstrated practical applicability for the accurate determination of the endogenous concentration of the target analytes in solid (fresh and FFPE breast human tissues) and liquid (human serum from colorectal and ovarian cancer patients) biopsies.…”
mentioning
confidence: 99%